Analisis Penghematan Penggunaan Energi Listrik Berbasis Fuzzy pada Hotel - Rifqi Wibowo; Sri Artini Dwi Prasetyowati; Agus Adhi Nugroho (Lembaga Pengembangan Kinerja Dosen, 2025)
Electricity is an important necessity, but its use must be managed wisely to avoid waste and negative environmental impacts. Energy-saving programs implemented in buildings encourage consumers to use energy more efficiently, reduce wasteful consumption that leads to inflated electricity bills, and serve as an initial step in overall energy management to lower total energy costs. Hotel Grand Dian Bumiayu showed an initial IKE of 27.77 kWh/m²/year. This figure, with a total energy consumption of 144,752.01 kWh/year, falls into the highly efficient category. This means the building's energy usage is already considered optimal compared to existing standards. Fuzzification calculations, using data from September 2023, yielded a DeFuzzification value of 12.858. This value is within the IKE range for the